2020
DOI: 10.3390/app10217813
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Dynamics in a Fragment of Brazilian Tropical Forest (Caatinga) over Consecutive Dry Years

Abstract: Increases in water scarcity due to climate change, especially in dry regions, can affect the dynamics of successional species. In view of the longest sequence of dry years (2010–2019) to have occurred in the Brazilian semi-arid region, with a consequent reduction in water availability, the influence of rainfall distribution on the production of above-ground plant biomass was investigated in a Dry Tropical Forest (DTF). This natural change monitoring experiment was conducted over 11 years (2009–2019) in a fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…On the other hand, the contribution of both the early and late secondary ecological groups generally tended to increase with the regeneration time (treatments), characterising a difference between the groups in carrying out their ecological functions during the regeneration process in the SDTF after clear-cutting. A greater abundance of individuals of species belonging to the pioneer ecological group has been seen in research in this forest formation [20,26].…”
Section: Community Structure 431 Density and Basal Area By Ecological...mentioning
confidence: 82%
See 2 more Smart Citations
“…On the other hand, the contribution of both the early and late secondary ecological groups generally tended to increase with the regeneration time (treatments), characterising a difference between the groups in carrying out their ecological functions during the regeneration process in the SDTF after clear-cutting. A greater abundance of individuals of species belonging to the pioneer ecological group has been seen in research in this forest formation [20,26].…”
Section: Community Structure 431 Density and Basal Area By Ecological...mentioning
confidence: 82%
“…ha −1 to 2113 ind. ha −1 over an 11-year period [26]. They also found that mortality was more related to the stage of plant development (younger plants being more prone to death) than to species.…”
Section: Community Structure 431 Density and Basal Area By Ecological...mentioning
confidence: 94%
See 1 more Smart Citation
“…This species has a broad geographic distribution and is also present in landscapes of the Brazilian seasonally dry tropical forest known as the Caatinga. B. cheilantha colonizes both primary and secondary forest formations with varying degrees of plasticity in various untested attributes in this study (Campos et al, 2020). We hypothesize that physiological traits will have a higher degree of change compared to morphological traits, potentially resulting in phenotypic plasticity.…”
Section: Introductionmentioning
confidence: 84%
“…March and April receive 43% of the annual rainfall [22], with a high occurrence of consecutive dry days [28,29]. The dry period occurs from June to December, with only 1% of the total annual rainfall [22], showing the high temporal variability of rainfall [28,30]. The annual potential evapotranspiration surpasses 2000 mm, which is within the 0.2 and 0.5 rainfall-to-potential evapotranspiration ratio described by [31] for semi-arid regions and has an aridity index of 0.48 [32] that also classifies the region as semi-arid, where water scarcity is observed 9 to 10 months per year [33].…”
Section: Study Areamentioning
confidence: 99%